STUDY ON THE USE OF HOUSEHOLD B3 WASTE AS BUILDING MATERIALSIN PAMENGKANG VILLAGE, KRAMATWATU DISTRICT, SERANG REGENCY - Ghina Rizqandi Qurrota A'yun; Dwi Aneka K (AGUSPATI RESEARCH INSTITUTA, 2024)
Building materials in architecture are usually applied in exteriors which include building facades, furniture in room interiors, or construction planning activities such as road infrastructure, for example road paving work, landscape work. In general, building materials are obtained from wood, concrete and steel. . Along with technological developments, building materials are also obtained from recycled materials, such as from household waste recycling management. Some waste that cannot be decompo sed is dangerous and toxic waste which we call B3 Waste (Hazardous and Toxic Materials). The study of the use of household hazardous waste as building materials can be applied in the exterior grouping which includes building facades, construction planning activities such as road infrastructure, for example road paving work, landscape and interior work which includes room furniture, and room decoration accessories as space aesthetics. The research method used is a qualitative method, which uses data collection techniques by conducting interviews, observations and questionnaires. with a sample of 33 respondents to then be analyzed descriptively regarding existing theories based on literature to see the achievements of aspects of the use of household hazardous waste as building materials in Pamengkang Village, Kramatwatu District, Serang Regency. The results of this research show that there are 3 building materials produced from solid B3 waste in the Pamengkang Village area, Kramatwatu, Serang, namely: Plastic, Glass, and Metal (Aluminum & Iron). These materials can be used in exteriors & building interiors according to their respective management methods (reuse and recycle.